Measurement of Basketball Physical Tests on Students Using an Outdoor Laboratory in the Education Park - Rinaldo, Pandu; Hartati, Hartati; Aryanti, Silvi (Department of Physical Education, Sport, Health and Recreation, 2023)
Tests and measurements are an integral part of various human activities, as well as in sports teaching and training activities, because by carrying out these two things one can find out the strengths and weaknesses of an athlete, so that ultimately can make the right decision. Physical abilities, especially in basketball, are very important in PJOK learning and to support daily activities. Therefore, students must have good physical condition. This study aims to determine the results of measuring the physical condition of basketball in Indralaya 2 Public Middle School students. This type of research is descriptive, using a quantitative approach using normality and percentage test data analysis. The population of this study were students of Indralaya 2 Public Middle School and the sample used was Indralaya 2 Middle School students totaling 70 people who were taken by chance. The instrument in this study used a test to measure physical condition in basketball, namely using a 50 meter running test (speed), sit ups (abdominal muscle strength), pullups (arm muscle strength), vertical jump (leg muscle strength), and 1000/800 m run (endurance). Data analysis techniques were processed using the Smirnov Kolmogorov normality test and percentages using the Excel and SPSS 22 programs. Based on the analysis of the data, the results of the measurement of the basketball physical test were included in the unfavorable category with a result of 32%. With the results that for the 50 meter run is 71.4%, sit ups are 33%, pull ups are 20%, vertical jumps are 36%, and 1000/800 m run are 4%. This means that for the measurement of the basketball physical test on Indralaya 2 Public Middle School students, their physical condition is not good. The application of this research is that the physical course is very supportive for daily activities, especially learning PJOK basketball material.Keywords: Physical Test Measurement, Basketball.